Quality of life in hematologic oncology patients undergoing chemotherapy - Andrade, Viviane; Sawada, Namie Okino; Barichello, Elizabeth (Revista da Escola de Enfermagem da USP, 2013)
This descriptive and cross-sectional study aimed to examine the socio-demographic/clinical aspects of health-related quality of life (HRQoL) and assess the HRQoL of onco- hematological patients undergoing chemotherapy. The data collection instrument was a socio-demographic/clinical questionnaire, the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC) QLQ-C-30. The sample consisted of 32 patients, eight of whom (25%) were diagnosed with Hodgkin's lymphoma; nine (28.12%), with non-Hodgkin's lymphoma; and 15 (46.87%), with leukemia. The data were analyzed using SPSS software. For the functional scales of the QLQ-C-30 (physical, cognitive, emotional, social and role performance), the mean scores ranged from 54.81 to 41.18, demonstrating an unsatisfactory level of functioning. In the symptom scales, there was a predominance of fatigue (64.57), insomnia (56.90) and loss of appetite (50.71). These symptoms interfered with the patients' physical functioning, demonstrating that the emotional and cognitive side effects of the treatment negatively influenced the HRQoL of the patients.